2022
DOI: 10.18063/ijb.v9i2.655
|View full text |Cite
|
Sign up to set email alerts
|

Steam-sterilized and degradable fused filament fabrication-printed polylactide/ polyhydroxyalkanoate surgical guides for dental implants: Are they accurate enough for static navigation?

Abstract: Three-dimensional (3D) printing is a rapidly evolving field and has gained increasing importance in the medical sector. However, the increasing usage of printing materials is accompanied by more wastages. With a rising awareness of the environmental impact of the medical sector, the development of highly accurate and biodegradable materials is of great interest. This study aims to compare the accuracy of polylactide/polyhydroxyalkanoate (PLA/PHA) surgical guides printed by fused filament fabrication and materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This result is in line with Gielisch et al. [ 46 ] who compared the behavior of polylactide/ polyhydroxyalkanoate (PLA/PHA) surgical guides printed by FFF and MED610 guides printed by MJ in fully guided dental implant placement before and after steam sterilization, and the study found significant deviations in angles and accuracy in the PLA/PHA guide as compared to the MED610 guide. MED610 and Surgical Guide resin can also be used for the production of custom-made medical devices to support treatments with materials needing skin or mucous contact for less than 24 h [ 47 , 48 ] .…”
Section: Discussionsupporting
confidence: 89%
“…This result is in line with Gielisch et al. [ 46 ] who compared the behavior of polylactide/ polyhydroxyalkanoate (PLA/PHA) surgical guides printed by FFF and MED610 guides printed by MJ in fully guided dental implant placement before and after steam sterilization, and the study found significant deviations in angles and accuracy in the PLA/PHA guide as compared to the MED610 guide. MED610 and Surgical Guide resin can also be used for the production of custom-made medical devices to support treatments with materials needing skin or mucous contact for less than 24 h [ 47 , 48 ] .…”
Section: Discussionsupporting
confidence: 89%
“…This contradiction might be explained by the different 3D-printing methods, i.e., PolyJet 3Dprinting in the aforementioned study vs. DLP 3D-printing in the current study, the different tested materials, the different types of specimens and the different assessment methods. A recent study focusing on the accuracy of steam-sterilized printed surgical guides concluded that, at the implant base level, a high and significant deviation in the angle as well as in the 3D accuracy was measured after steam sterilization [39]. This study tested polylactide and polyhydroxyalkanoate surgical guides printed with the fused filament fabrication process and conducted a different methodology [39].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study focusing on the accuracy of steam-sterilized printed surgical guides concluded that, at the implant base level, a high and significant deviation in the angle as well as in the 3D accuracy was measured after steam sterilization [39]. This study tested polylactide and polyhydroxyalkanoate surgical guides printed with the fused filament fabrication process and conducted a different methodology [39]. Another study tested the linear dimensional accuracy of SLA surgical guides, in contrast to our study, where all the guides were printed by the DLP process [40].…”
Section: Discussionmentioning
confidence: 99%